Analisis Penggunaan Tertinggi dan Terbaik pada Tanah Kosong di Pantai Manggar Segara Sari Kecamatan Balikpapan Timur - Maulana, Indra; Zulfikar, Akbar Lufi; Mahardika, Swadia Gandhi (IJMA (Indonesian Journal of Management and Accounting), 2023)
Analysis of the highest and best use to government-owned vacant land located in Manggar Segara Sari Beach, East Balikpapan, done by the analysis of productivity and the physical aspects of the property include the location as well as the legal and regulatory aspects in order to obtain alternative uses which allows. Next step is about market analysis which is analyze market demand and supply, also financial feasibility study for every alternative.In this study, the data were analyzed consist of primary data and secondary data. Primary data includes data revenues, rents and expenditure proposed as an alternative to the use, obtained by structured interview form, while the physical data which includes the size, shape of the tread, topography, utilities and others obtained through direct observation. Secondary data available at government office such as BPKAD (Badan Pengelolaan Keuangan dan Aset Daerah), Badan Pusat Statistik, and many others.Based on the results of the market analysis, the proposed use of the third consists of cottages, restaurants, and mixed use eligible to proceed to the stage of financial analysis. Based on the financial feasibility indicators Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Rate Return on Investment (ROI), dan Benefit Cost Ratio (BCR), Mixed use is better than cottage and restaurant that can be conclude mixed use is the highest and best use.